A pedagogical paradigm for enhancing motivation and mastery in history education: Exploring the efficacy of Ehsond intervention - Nurulasyikin Binti Hassan, Anizah Binti Mohd Salleh, Zainun binti Mustafa, Siti Zahrah binti Mahfood, Murihah binti Abdullah (Tanjung Malim, 2024)
A pedagogical paradigm for enhancing motivation and mastery in history education: Exploring the efficacy of Ehsond intervention by Nurulasyikin Binti Hassan, Anizah Binti Mohd Salleh, Zainun binti Mustafa, Siti Zahrah binti Mahfood, Murihah binti Abdullah